fMR-adaptation reveals invariant coding of biological motion on human STS - Grossman, Emily D.; Jardine, Nicole L.; Pyles, John A. (Frontiers in Human Neuroscience, 2010)
Neuroimaging studies of biological motion perception have found a network of coordinated brain areas, the hub of which appears to be the human posterior superior temporal sulcus (STSp). Understanding the functional role of the STSp requires characterizing the response tuning of neuronal populations underlying the BOLD response. Thus far our understanding of these response properties comes from single-unit studies of the monkey anterior superior temporal sulcus (STSa), which has individual neurons tuned to body actions, with a small population invariant to changes in viewpoint, position and size of the action being viewed. To measure for homologous functional properties on the human STS, we used fMR-adaptation to investigate action, position and size invariance. Observers viewed pairs of point-light animations depicting human actions that were either identical, differed in the action depicted, locally scrambled, or differed in the viewing perspective, the position or the size. While extrastriate hMT+ had neural signals indicative of viewpoint specificity, the human STS adapted for all of these changes, as compared to viewing two different actions. Similar findings were observed in more posterior brain areas also implicated in action recognition. Our findings are evidence for viewpoint invariance in the human STS and related brain areas, with the implication that actions are abstracted into object-centered representations during visual analysis.